How Does Fusarium oxysporum Sense and Respond to Nicotinaldehyde, an Inhibitor of the NAD+ Salvage Biosynthesis Pathway? - Anand, Gautam; Waiger, Daniel; Vital, Nuria; Maman, Jacob; Ma, Li Jun; Covo, Shay (Frontiers in Microbiology, 2019)
Plant pathogenic fungi are a major threat to food security and impose a severe economic burden, thus there is a continuous need to develop new strategies to manage them. NAD+ is a co-factor in numerous enzymatic activities and determines the metabolic fate of the cell. Therefore, maintenance of NAD+ concentration is important for cellular viability. Consequently, the NAD+ biosynthetic pathway and redox homeostasis was suggested as a target for antifungal development. We aimed to study how Fusarium oxysporum senses and responds to nicotinaldehyde (NA), an inhibitor of Pnc1 and a key enzyme in the salvage pathway of NAD+ biosynthesis. We were able to show that NA was inhibitory in high concentrations to several fungal plant pathogens, with much milder effects on tomato growth. Under low nutrient conditions NA reduced the total amounts of NAD+ in the fungal cell, a trend that was also observed in rich media, although without statistical significance. In low and high nutrient availability NA reduced dramatically the NAD+/NADH ratio. After exposure to NA, NADH levels were up and NAD+ levels and the biomass were greatly reduced. Cells responded to NA by up-regulation of oxidoreductases, with hardly any up-regulation of the classic response to oxidative stress. Direct measurement of oxidative stress response showed that unlike formaldehyde and hydrogen peroxide NA caused reductive rather than oxidative stress. Surprisingly, alcohol dehydrogenases were significantly up-regulated more than any other dehydrogenases, including aldehyde dehydrogenases. We propose that conidia of F. oxysporum efficiently detoxified the aldehyde group of NA by reducing NAD+ to NADH; the high concentrations of the latter provoked the expression of alcohol dehydrogenases that in yeast can act to reduce NADH and increase NAD+ amounts, respectively. Overall, the results suggest that targeting NAD+ biosynthesis pathway and redox homeostasis can be a potential approach to manage fungal plant pathogens. Many of the natural antifungal compounds produced by bio-control agents or even the natural biome are aldehydes, and thus the results presented here predict the possible response of Fusarium to wide sources of toxicity in the environment.